Novels of Theodore Dreiser : a Critical Study. - Pizer, Donald (University of Minnesota Press, 1976)
Relying heavily on the manuscripts and letters in the Dreiser Collection of the University of Pennsylvania Library, Professor Pizer seeks to establish the facts of the sources and composition of each of Dreiser's eight novels and to study the themes and form of the completed works. In this study he relates what can be discovered about the factual reality of a novel to its imaginative reality. His interpretation of the novels avoids the suggestion that there is a single overriding theme or direction in Dreiser's work and emphasizes that Dreiser deserves examination primarily on the basis of the.